A z‐gradient array coil with a dedicated active‐shielded array coil for MRI. Issue 6 (2nd August 2022) - Takrimi, Manouchehr; Atalar, Ergin
Abstract : Purpose: An array‐based z ‐gradient coil with a set of programmable power amplifiers can outperform a conventional z ‐gradient coil and make it highly customizable with a broader range of tunable features. Methods: A dynamically adjustable imaging volume can be achieved using a pair of independent arrays and a modified optimization procedure based on analytic equations. Two modes of operation are provided: (a) standard mode that resembles a conventional coil; (b) advanced mode, where all performance parameters can be adjusted employing a controllable feeding mechanism. Commercial software is used to demonstrate the validity and feasibility of the proposed coil. Results: Primary and shield array diameters are 24 and 30 cm, both of which comprise 12 bundles of 10 turns copper wires. Maximum feeding voltage/current is 250 V/100 A for all array elements. Four distinct magnetic profiles are provided: (a) conventional profile with 140 mm diameter spherical region of interest, 120 mT/m gradient, and up to 4500 T/m/s slew rate; (b) profile of 200 mT/m, 70 mm region of interest, and up to 6900 T/m/s slew rate; (c) 60 mm axially shifted 70 mm region of interest with 120 mT/m strength and 3600 T/m/s slew rate; and (d) profile of 370 mT/m, 120 mm region of interest, and 3700 T/m/s slew rate when the active shield is reverse fed. Conclusion: By using an active‐shielded gradient array coil, the magnetic field profile of the imaging volume can be adjusted dynamically, and it can provide new features and a wide range of field profiles for diverse applications in MRI.